2010
DOI: 10.1161/circulationaha.109.927921
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Implications of Mitral Regurgitation in Patients With Severe Aortic Regurgitation

Abstract: Background— Mitral regurgitation (MR) is common in those with severe aortic regurgitation (AR) and can predispose to atrial fibrillation, heart failure, and a need for mitral valve surgery during aortic valve replacement (AVR). However, little data exist as to its clinical and prognostic implications. Methods and Results— Search of our echocardiographic data base between 1993 and 2007 yielded 756 patients with se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 11 publications
(8 reference statements)
1
49
1
Order By: Relevance
“…One should keep in mind that although this patient population is younger and has a lower logEuroSCORE I, it is at higher risk for adverse survival since the response of the left ventricle (LV) after treatment of AR is quantitatively and qualitatively different from AS, mechanistically related to a larger LV with thinner walls and lower ejection fraction . In fact, 50% of patients in our cohort had moderate/severe MR, which is not only an independent predictor of mortality but also weakens the positive effect of TAVR on survival . Of note, significant MR was also frequent in an early experience of first‐generation THV for predominant AR .…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…One should keep in mind that although this patient population is younger and has a lower logEuroSCORE I, it is at higher risk for adverse survival since the response of the left ventricle (LV) after treatment of AR is quantitatively and qualitatively different from AS, mechanistically related to a larger LV with thinner walls and lower ejection fraction . In fact, 50% of patients in our cohort had moderate/severe MR, which is not only an independent predictor of mortality but also weakens the positive effect of TAVR on survival . Of note, significant MR was also frequent in an early experience of first‐generation THV for predominant AR .…”
Section: Discussionmentioning
confidence: 75%
“…Also logEuroSCORE I was lower but LV function was more frequently impaired (30–50% in 13.3% and <30% in 30.0%). In fact, the most common comorbidity in our cohort was significant MR, which is generally frequent in patients with AR being severe in 25% of patients . In these patients, MR is a reflection of impaired LV function due to volume overload secondary to AR.…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, performing AVR plus concomitant mitral valve repair was associated with improved survival. These data suggest that the development of MR might provide useful information about the timing of surgery in patients with AR 37. Doctors are often reluctant to offer AVR to patients with severe AR and associated severe LV dysfunction (EF≤35%), yet a recent study has shown that it results in significantly improved 5-year survival rates of 70% as compared with 37% for patients not receiving surgery.…”
Section: Aortic Regurgitationmentioning
confidence: 99%
“…1,2 The left ventricular (LV) pressure and volume overload caused by significant AR leads to LV dilation, with subsequent changes in papillary muscle position and tethering of the mitral leaflets, which may cause coaptation failure and regurgitation. The prognostic implications of concomitant secondary MR in patients with significant AR are not benign, and it has been shown that mitral valve surgery in addition to aortic valve surgery is associated with better prognosis.…”
mentioning
confidence: 99%
“…The prognostic implications of concomitant secondary MR in patients with significant AR are not benign, and it has been shown that mitral valve surgery in addition to aortic valve surgery is associated with better prognosis. 2 However, it remains unclear why some patients with significant AR have concomitant significant secondary MR while other patients do not show MR. 1 A pioneer study using three-dimensional transthoracic echocardiography suggested that patients with significant AR show significantly larger total mitral leaflet area compared with patients without AR, which may reflect mitral leaflet remodeling to prevent failure of mitral leaflet coaptation. 1 However, changes in mitral valve geometry, including the subvalvular apparatus in patients with significant AR, have not been evaluated.…”
mentioning
confidence: 99%